Kinerja Keuangan Dan Kelembagaan Badan Keswadayaan Masyarakat Ngudi Makmur Desa Klumprit Kecamatan Mojolaban Kabupaten Sukoharjo - Trisnowati, Juni; Suryani, Puput Ike (Responsibilitas, 2011)
Abstract The purpose of this study is to determine the financial performance and institutional performance in BKM Ngudi Makmur in Klumprit Village, Mojolaban Sukoharjo. This research was accomplished by using surveys. The population in this study is that all the board as many as 68 people, with a sample of 13 people Method of data collection by interview, observation and documentation, while the methods of data analysis conducted by qualitative analysis with an interactive model. Results of analysis of performance measurement that views of the monitoring and financial reporting consistently shown that there is significant influence between financial performance and institutional performance in the smooth and success in BKM Ngudi Makmur. Keywords : Financial performance and Institutional performance.